Goals of Teaching Foreign Languages - Bahrombekova Munisa Mansurovna (Journal of Higher Education and Academic Advancement, 2024)
In this article, the question of why a foreign language is taught in higher education can be answered that a foreign language is studied for practical, educational, educational and developmental purposes. A foreign language is studied for 4 purposes.